Brain stimulation and constraint for hemiparesis after perinatal stroke: The PLASTIC CHAMPS trial. (3rd June 2015) - Kirton, A; Andersen, J; Herrero, M; Carsolio, L; Nettel-Aguirre, A; Mineyko, A; Hill, M
Abstract : Background: Perinatal stroke causes hemiparetic cerebral palsy. Constraint therapy (CIMT) improves function in congenital hemiparesis and adult stroke. Repetitive transcranial magnetic stimulation (rTMS) may improve function in adult stroke. The two have not been tested in perinatal stroke. Methods: PLASTIC CHAMPS (www.clinicaltrials.gov/NCT01189058 ) was a controlled factorial trial of rTMS and CIMT in perinatal-stroke hemiparesis. Children 6-18 years participated in a 2 week peer-supported motor learning camp, randomized to daily inhibitory rTMS (1200 stimulations, contralesional M1), CIMT, both or neither. Primary outcomes were Assisting Hand Assessment (AHA) and Canadian Occupational Performance Measure (COPM) at 1, 8, and 24 weeks. Quality-of-life, safety and tolerability were evaluated. Change was assessed across treatment groups over time (linear mixed effects model). Results: All forty-five subjects completed the trial (median 11.4yrs). COPM scores increased >100% with maximal gains at 6 months (p<0.002). Addition of rTMS and/or CIMT doubled the chances of clinically significant gains. Combined rTMS+CIMT resulted in larger AHA gains at all time points (6 months p=0.006). CIMT or rTMS alone had more modest effects. Neither treatment decreased function in either hand. Procedures were well tolerated. Conclusions: Children with hemiparesis participating in intensive, psychosocial rehabilitation programs perceive marked increases in function. Non-invasive brain stimulation may enhance motor learning therapy in perinatal stroke hemiparesis.